Homestay Development For Backpacker Tourism In Indonesia: A Forecasting Analysis - Purusottama, Ambara; Trilaksono, Teddy; Dewantara, Made Handijaya; Prastowo, Gregorius Dimas Hapsoro (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Backpacker tourism is an alternative tourism development for new destinations in Indonesia. Utilizing homestays managed by indigenous people in this new tourism field will improve the local economy. However, studies related to backpacker tourists and the availability of homestays have not yet been done. This study thus analyzes supply and demand in ten New Bali destinations using five-year modeling and those projections and finds a distribution problem regarding the number of homestays in some of these destinations. Some are already oversupplied; others still need more homestays for backpacker tourists. These results contribute as a reference for policymakers and other stakeholders when reformulating homestay development in the future for ten New Bali destinations. The findings contribute to the current research agenda of homestay development particularly to capture the backpacker tourism in Indonesia, align with the current tourism development agenda in rural area.